The Health Effects of Economic Growth: Evidence from PM2.5-Attributable Mortality in China - Cheng Xue; Yiying Chao; Shangwei Xie; Kebiao Yuan (Economies)
Economic growth can bring material prosperity and improvements in public services to a country yet can simultaneously lead to environmental pollution that threatens population health, which has important implications for shaping macro-level policies. Here, we investigate the relationship between economic growth and mortality attributable to air pollution in China from 2002 to 2021, using data analyzed with Stata 18 software. We identify a counterintuitive U-shaped relationship between the two, with the coefficient of the primary term for economic growth at −1.222 and the quadratic term at −0.053, both statistically significant at the 1% level. The inflection point, with accounting for control variables, is calculated to be 99,708 yuan (CNY) per person. These results withstand different empirical testing. We then perform heterogeneity analyses at the city level and find that disparities in social, economic, and physical geographical conditions lead to an unequal mortality burden that persists. Economic growth may have negative impacts on population health after crossing a certain threshold, although the effects vary across different regions. Our findings reveal that the benefits of economic growth may not “trickle down” to improve population health. Policymakers cannot take economic growth as an intrinsic good that would inevitably lead to better population health. Greater emphasis should be placed on egalitarian welfare systems, investments in environmental improvements, and other life-supporting priorities, as these measures could mitigate the negative health impacts of economic growth and promote a virtuous cycle between the economy and population health.